Effects of cathodal transcranial direct current stimulation on inhibitory and attention control in children and adolescents with attention-deficit hyperactivity disorder: A pilot randomized sham-controlled crossover study. (June 2022) - Klomjai, Wanalee; Siripornpanich, Vorasith; Aneksan, Benchaporn; Vimolratana, Oranich; Permpoonputtana, Kannika; Tretriluxana, Jarugool; Thichanpiang, Peeradech
Abstract: The pathophysiological of attention-deficit hyperactivity disorder (ADHD) includes hypoactivation of the dorso-lateral prefrontal cortex (DLPFC). Most studies have used anodal (excitatory) transcranial direct current stimulation (tDCS) to improve ADHD symptoms, however, a meta-analysis showed limited effect on improving inhibition, and no evidence of attention improvement. We thus present a pilot protocol for investigating the effect of other montage i.e. cathodal (inhibitory) tDCS on neurophysiological and behavioral measures in ADHD. Eleven participants underwent active (1.5 mA, 20 min) and sham cathodal tDCS over the left DLPFC for 5 consecutive days at a 1-month interval. Quantitative electroencephalography was recorded in a resting state with the eyes opened and closed during visual go/no-go and auditory continuous performance tasks at baseline, after five sessions, and at 1-week and 1-month follow-ups. Correct responses and omission errors were recorded. After five active sessions, alpha power increased in the right frontal area when the eyes were opened, and delta power in the left frontal area and omission errors decreased during go/no-go tasks, with no differences at follow-ups. The results revealed improvements in inhibitory control, but not for attention. No aftereffects were observed in either outcomes. However, the changes found in both hemispheres would probably support the hypothesis that cathodal stimulation over the left DLPFC may increase the activity of the right DLPFC via transcallosal inhibition. Results of this pilot trial would help to design and implement a full-scale randomized control trials for further ADHD research. This study was registered on ClinicalTrials.gov (NCT03955692). Highlights: 5-sessions of cathodal tDCS over the left DLPFC increased alpha power in the right frontal area at resting-state eyes open. During the visual go/no-go task, it decreased delta power in the left frontal area and reduced omission errors. However, no changes of either EEG data or behavior data during auditory continuous performance task. These results revealed improvements in inhibitory control, while the outcome measures for attention control were unchanged. This pilot study may pave the way for conducting larger studies to establish the optimal tDCS protocol for ADHD intervention.